Matematika pro elektromagnetismus - Rára, Michael (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Cílem práce je pomocí vybraných kapitol matematiky, konkrétně tenzorů, vektorových polí, orientovaných křivkových a plošných integrálů a integrálních vět, popsat elektromagnetické zákony včetně odvození Maxwellových rovnic pomocí diferenciálního, integrálního i tenzorového počtu s následnou ukázkou užitečnosti tenzorového zápisu těchto rovnic.

The goal of this thesis is the description of elektromagnetism by means of selected parts of mathematics, in particular tensors, vector fields, integral calculus and integral theorems. Maxwell's equations will be derived by means of these notions in integral form, differential form and tensor form, we also show usefulness of tensor form of these equations.
Mathematics for Electromagnetism
Keywords: Elektromagnetismus; Tenzory; Vektorová pole; Integrální věty; Maxwellovy rovnice.; Elektromagnetism; Tensors; Vector fields; Integral theorems; Maxwell's equations.